Appetitive traits and their associations with metabolic health outcomes among adults living with prediabetes: Results from a cross-sectional study - Azize Nur Yildirim; Raj Ahluwalia; Julia Kathrin Baumgart; Tamara R. Cohen; Megan M. Macpherson; Mary E. Jung; Sarah A. Purcell (PLoS ONE, 2026)
Appetitive traits influence eating behaviours and energy balance, potentially affecting obesity and type 2 diabetes (T2D) risk. However, evidence is limited on how these traits relate to metabolic outcomes, including body mass index (BMI), waist circumference (WC), and hemoglobin A1c (HbA1c), which are key risk factors for T2D. This study aimed to (1) characterize appetitive traits (Food Responsiveness, Emotional Overeating, and Slowness in Eating) in female and male adults living with prediabetes and (2) examine their associations with metabolic outcomes. Adults with prediabetes were enrolled in this cross-sectional analysis. Appetitive traits were assessed using the Adult Eating Behaviour Questionnaire. Metabolic outcomes included measured BMI, WC, and HbA1c. Associations between appetitive traits and metabolic outcomes were assessed using Spearman rank correlation coefficients (rs), stratified by sex. A total of 115 adults were included (mean age: 61.8 ± 10.9 years; 64.3% female). Females had mean BMI of 31.61 ± 6.33 kg/m², WC of 100.58 ± 13.92 cm, and HbA1c of 5.83 ± 0.25%; males had mean BMI of 32.29 ± 5.70 kg/m², WC of 112.51 ± 14.62 cm, and HbA1c of 6.00 ± 0.28%. Food Responsiveness positively correlated with BMI (rs = 0.414, p < 0.001) and WC (rs = 0.459, p < 0.001) only in females. In males, Emotional Overeating positively correlated with HbA1c (rs = 0.449, p = 0.003), while Slowness in Eating negatively correlated with HbA1c (rs = −0.325, p = 0.038). Appetitive traits were moderately and significantly associated with metabolic outcomes, with associations differing by sex. Identifying sex-specific mechanisms may inform interventions targeting appetitive traits to improve metabolic health in adults with prediabetes.